Assessment of a naturally occurring high background radiation area with elevated levels of thorium along coastal Odisha, India using radiometric methods. (November 2021) - Ghosal, Shayantani; Agrahari, Sudha; Banerjee, Debashish; Sengupta, Debashish
Abstract: The present study evaluates the enrichment and distribution of radioelements along the eastern coast of India. India possesses the second largest reserve of thorium bearing monazite in the world, in terms of heavy minerals present primarily along its long coastline. Radioelement estimation of about 30 km long beach area along the eastern coast of India is reported and implications discussed. A total number of 822 data points were studied using a portable Geiger Muller counter, to estimate the variation of dose rates, due to the ambient radionuclides along two different trends. One was parallel (northeast-southwest) and the second one perpendicular to the coastline. Pre-selected samples from in-situ radiometric surveys on the heavy mineral placers were studied further, for quantitative estimation of the abundance of radioactive elements primarily uranium and thorium, using a High Purity Germanium detector. Radioelement concentration assessment of core samples (depth 2 m), were studied from two different beaches. Radiological parameters like radium equivalent, annual effective doserate and absorbed dose rate has been calculated based on the 238 U, 232 Th and 40 K concentrations. Heavy mineral placers along the shoreline indicate a very high thorium (avg - 2990.22 Bq kg −1 ) which is due to the extensive distribution indicative of monazite. The coastal area also exhibits relatively low uranium (avg - 319.1 Bq kg −1 ). Based on its high thorium concentration, the area can be considered as a high natural background radiation area . Based on the concentrations of uranium and thorium, the weathering conditions and depositional environment prevalent along the beach areas have been discussed. Graphical abstract: Image 1 Highlights: Dose rate variation along a 30 km stretch of eastern coastal beach areas of India is reported and presented in Isorad map. Activity concentration of 238 U, 232 Th and 40 K measured by gamma spectrometry is estimated and presented in Isorad map. Radiation parameters are calculated and discussions based on their possible relation with the radio-elements are provided. Radioelement concentration of charnockite, khondalite and granite from EGMB is estimated and possible provenance discussed. Variation of the activity concentration of 238 U, 232 Th and 40 K of the subsurface has been estimated from two shallow cores. Depositional environment based on the 238 U, 232 Th and 40 K concentration of the beach sands have been investigated.